Flexible NbTiN thin films for superconducting electronics - Rezinovsky Nieto, S. J.; Hofer, Juan Andres; Sirena, Martin; Haberkorn, Nestor Fabian (Elsevier Science, 2023)
Fil: Rezinovsky Nieto, S. J.. Universidad Tecnológica Nacional. Facultad Regional la Rioja; Argentina. Comisión Nacional de Energía Atómica. Centro Atómico Bariloche; Argentina